How Comics Help to Teach Shakespeare in Schools - Maynard, The University of Adelaide, Australia, Amy Louise (Asiatic: IIUM Journal of English Language and Literature, 2013)
To address the literacy crisis that is currently affecting Britain, and to engage students in English studies in Australia, teachers and educators are turning to graphic novels; specifically, graphic novel adaptations of Shakespeare’s plays. Whilst there have been critics of this approach, teaching children about Shakespeare and poetry through comics appears to be successful. There have already been multiple examples of the younger generation becoming familiar with Shakespeare through pop culture, and graphic novels have the advantage in that they have been proven to improve literacy rates. It is a belief of prominent Shakespearean scholars that the works of Shakespeare should not be limited to the elite, as his themes, characters and most importantly, language, is universal, and can be interpreted in many different ways.